Achieving High Efficiency and Eliminating Degradation in Solid Oxide Electrochemical Cells Using High Oxygen‐Capacity Perovskite. (8th September 2016) - Jun, Areum; Kim, Junyoung; Shin, Jeeyoung; Kim, Guntae
Abstract: Recently, there have been efforts to use clean and renewable energy because of finite fossil fuels and environmental problems. Owing to the site‐specific and weather‐dependent characteristics of the renewable energy supply, solid oxide electrolysis cells (SOECs) have received considerable attention to store energy as hydrogen. Conventional SOECs use Ni‐YSZ (yttria‐stabilized zirconia) and LSM (strontium‐doped lanthanum manganites)‐YSZ as electrodes. These electrodes, however, suffer from redox‐instability and coarsening of the Ni electrode along with delamination of the LSM electrode during steam electrolysis. In this study, we successfully design and fabricate highly efficient SOECs using layered perovskites, PrBaMn2 O5+ δ (PBM) and PrBa0.5 Sr0.5 Co1.5 Fe0.5 O5+ δ (PBSCF50), as both electrodes for the first time. The SOEC with layered perovskites as both‐side electrodes shows outstanding performance, reversible cycling, and remarkable stability over 600 hours.